Clinicopathological Review of 547 Bulbar Enucleations in Hungary (2006–2017) - Gábor Tóth; Nóra Szentmáry; Gábor László Sándor; Béla Csákány; Erika Maka; Jeannette Tóth; Zsuzsanna Antus; Milán Tamás Pluzsik; Achim Langenbucher; Zoltán Zsolt Nagy; Olga Lukáts (Journal of Ophthalmology)
Purpose. To analyse current clinicopathological enucleation indications in a large third-referral centre in a developed country (Hungary) over a period of 12 years. Methods. Retrospective review was performed on 547 enucleated eyes of 543 patients (48.6% males, age 52.7 ± 24.5 years) who were operated on between 2006 and 2017 at the Department of Ophthalmology of Semmelweis University, in Budapest, Hungary. For each subject, clinicopathological data, including patient demographics, indications for enucleation, B-scan ultrasound reports, operative details, and histopathological analyses, were reviewed. Primary enucleation indications were classified into trauma, tumours, systemic diseases, surgical diseases, infections or inflammations, miscellaneous diseases, and unclassifiable groups. Clinical immediate enucleation indications were classified as tumours, atrophia or phthisis bulbi, infection or inflammation, painful blind eye due to glaucoma, acute trauma, threatening or spontaneous perforation, cosmetic causes, and expulsive bleeding. Results. The most common primary enucleation indications were tumours (47.3%), trauma (16.8%), surgical diseases (15.7%), infection or inflammation (11.6%), systemic diseases (5.1%), miscellaneous diseases (2.0%), and unclassifiable diseases (1.5%). Clinical immediate enucleation indications were tumours (46.1%), atrophia or phthisis bulbi (18.5%), infection or inflammation (18.5%), painful blind eye due to glaucoma (11.2%), acute trauma (3.7%), threatening or spontaneous perforation (1.3%), cosmetic reasons (0.5%), and expulsive bleeding (0.4%). Conclusions. Intraocular tumours represent the most common clinicopathological indication for ocular enucleation in our study population. Following ocular trauma and systemic diseases, the rate of enucleation decreased in the last decade, compared to those previously reported in other developed countries. However, changes were not observed for surgical diseases, infectious and inflammatory causes, or for miscellaneous and unclassified diseases. Orbital implant financing should be increased to ensure better postoperative aesthetic rehabilitation, following enucleation in Hungary.